1999
DOI: 10.1016/s0893-133x(98)00130-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Anti-Serotonin and Serotonin Anti-Idiotypic Antibodies Are Elevated in Panic Disorder

Abstract: The psychoneuroimmunology of panic disorder is relatively unexplored. Alterations within brain stress systems that secondarily influence the immune system have been documented. A recent report indicated elevations of serotonin (5-HT) and ganglioside antibodies in patients with primary fibromyalgia, a condition with documented associations with panic disorder. In line with our interest in dysregulated 5-HT systems in panic disorder (PD), we wished to assess if antibodies directed at the 5-HT system were elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…As other studies of clotting factors and related measures have observed and referred to as a “batch effect” 8488 , we noted that all four hemostasis measures varied systematically by WIHS site / laboratory testing date of the sample units. As these previous studies concluded, this likely reflected differences in sample preparations and testing and were not of direct interest to the analysis; we thus adjusted for these WIHS site / laboratory test date “batch effects” when performing our analyses of markers of hemostasis in an approach analogous to age adjustment 89 .…”
Section: Methodssupporting
confidence: 62%
“…As other studies of clotting factors and related measures have observed and referred to as a “batch effect” 8488 , we noted that all four hemostasis measures varied systematically by WIHS site / laboratory testing date of the sample units. As these previous studies concluded, this likely reflected differences in sample preparations and testing and were not of direct interest to the analysis; we thus adjusted for these WIHS site / laboratory test date “batch effects” when performing our analyses of markers of hemostasis in an approach analogous to age adjustment 89 .…”
Section: Methodssupporting
confidence: 62%
“…Dopaminergic and serotonergic drugs are used to treat motor and psychiatric symptoms, respectively, in patients affected by GAS-related neuropsychiatric disorders (Demiroren et al, 2007; Gabbay and Coffey, 2003; Moretti et al, 2008; Murphy et al, 2010; Swedo and Grant, 2005; Swedo et al, 1993). Finally, immunoreactivity to different components of the serotonergic system, such as serotonin and serotonin receptors, has been reported in sera from panic disorder and rheumatoid arthritis patients (Coplan et al, 1999; Maes et al, 2013; Schott et al, 2003; Tanaka et al, 2003), and sera from SC and PANDAS patients reacted with D1 and D2 receptors (Brimberg et al, 2012; Cox et al, 2013; Dale et al, 2012). Interestingly, Dale et al (2012) have recently found antibodies against surface D2 receptors in the sera of patients suffering from basal ganglia encephalitis, which is characterized by motor (including, parkinsonism, dystonia and chorea), and psychiatric symptoms (including, emotional lability, attention deficit and psychosis), which are also found in GAS-related neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…HCs [24,[38][39][40][41][42][43] ↑ vs. HCs [42,44] 5-HIAA CSF levels =vs. HCs [45] ↓ in patients with positive response to TCAs [45] ↑ in MDD females with comorbid PDA vs. patients without comorbid PDA and vs. HCs [46] 5-HIAA jugular venous overflow ↑ vs. HCs [47] Plasma anti-5-HT and 5-HT anti-idiotypic antibodies ↑ vs. HCs [48] Dopaminergic system D plasma level ↑ vs. HCs [49] GH levels in response to apomorphine ↑ vs. MDD [50] HVA CSF concentration =vs. HCs [45] Noradrenergic system E plasma levels ↑ vs. HCs [49] Platelet aggregation in response to NE, platelet α-2-receptor density, and lymphocyte β-receptor density before and after TCAs treatment ↑ vs. HCs [35] Tritiated clonidine binding (to measure platelet α-2-adrenoceptors) ↓ vs. HCs [51] Standing plasma NE ↑ vs. HCs [51] Beta-2-adrenoceptor density in both lying and standing position ↑ vs. HCs [52] Plasma MHPG in alcoholics with PDA ↑ vs. alcoholics without PDA [53] GABAergic system BDZ receptor sensitivity (measured by the severity of panic attacks after flumazenil intravenous injection) ↑ vs. HCs [54] GABA agonistic 3α-reduced neurosteroids ↑vs.…”
Section: Serotoninergic Systemmentioning
confidence: 99%